Exploring the causal effects of the gut microbiome on serum lipid levels: A two-sample Mendelian randomization analysis - Guo, Gongjie; Wu, Yonglin; Liu, Yingjian; Wang, Zixian; Xu, Guifeng; Wang, Xipei; Liang, Feiqing; Lai, Weihua; Xiao, Xiao; Zhu, Qian; Zhong, Shilong (Frontiers in Microbiology, 2023)
Background: The gut microbiome has been reported to be associated with dyslipidemia in previous observational studies. However, whether the composition of the gut microbiome has a causal effect on serum lipid levels remains unclear. Objective: A two-sample mendelian randomization (MR) analysis was conducted to investigate the potential causal relationships between gut microbial taxa and serum lipid levels, including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and log-transformed triglyceride (TG) levels. Materials and Methods: Summary statistics of genome-wide association studies (GWASs) for the gut microbiome and the four blood lipid traits were obtained from public datasets. Five recognized MR methods were applied to assess the causal estimates. Among which, the inverse-variance weighted (IVW) regression was used as the primary method. A series of sensitivity analyses were performed to test the robustness of the causal estimates. Results: The combined results from the five MR methods and sensitivity analysis showed 59 suggestive causal associations and four significant causal associations. In particular, genus Terrisporobacter was associated with higher LDL-C (PIVW=3.01×10−6) and TC levels (PIVW=2.11×10−4), phylum Actinobacteria was associated with higher LDL-C level (PIVW=4.10×10−4), and genus Oscillospira was associated with lower TG level (PIVW=2.19×10−6). Conclusions: This study may provide novel insights into the causal relationships of gut microbiome on serum lipid levels and new therapeutic strategies or prevention for dyslipidemia.